37 Incidence and one year outcome of periprocedural myocardial infarction following cardiac surgery: are the universal definition and scai criteria fit for purpose?. (4th June 2021) - Hinton, Jonathan; Augustine, Maclyn; Gabara, Lavinia; Mariathas, Mark; Allan, Rick; Borca, Florina; Nicholas, Zoe; Ikwoube, John; Gillett, Neil; Kwok, Chun Shing; Cook, Paul; Grocott, Michael; et al.
Abstract : Introduction: The diagnosis and clinical implication of periprocedural myocardial infarction (PPMI) following coronary artery bypass grafting (CABG) is contentious, especially given its importance in the interpretation of trial data. Two accepted definitions of PPMI yield discrepant results. Little is known about the association between the diagnosis of PPMI, using high sensitivity troponin (hs-cTn), and medium term mortality in patients who undergo CABG, either alone or in conjunction with another procedure. Method: Consecutive patients admitted to a cardiothoracic critical care unit (CCCU) over a six month period following open cardiac surgery had hs-cTnI assay performed on admission and every day for forty-eight hours, regardless of whether there was a clinical indication. Patients were categorised as PPMI using both the Universal Definition of MI (UDMI) and Society of Cardiovascular Angiography and Interventions (SCAI) criteria. Comorbidity data, surgical details and clinical progress in CCCU were recorded. One year mortality data were obtained from NHS Digital. Results: There were 245 CABG patients, of whom 20.4% met criteria for UDMI PPMI and 87.6% for SCAI UDMI. The diagnosis of UDMI PPMI was independently associated with one year mortality (hazard ratio 4.175 (95% confidence interval 1.281 – 13.608)), whereas there was no association between SCAI PPMI and one year mortality ( figure 1 ). Of the 243 patients who had non CABG cardiac surgery, 11.4% met criteria for UDMI PPMI and 85.2% for SCAI PPMI but neither was associated with one year mortality. Conclusions: The incidence of SCAI PPMI in a real world cohort of cardiac surgery patients is so high as to be of limited clinical value. By contrast, a diagnosis of UDMI PPMI post CABG is independently associated with one year mortality, so may have clinical utility. Conflict of Interest: Beckman Coulter provided the assays used in my research but had no other role in the studies